'Australia – Drive It Like You Stole It'*: automobility as a medium of communication in settler colonial Australia. Issue 4 (4th July 2017) - Clarsen, Georgine
Abstract: More than a means of transportation, the global system of automobility is simultaneously a meaning-making assemblage. In Australia automobility was central to the formation of a settler colonial polity, and its pervasive mediatization trumpeted settlers' legitimate possession of the continent. The rich archives of settler automobilism are not matched, however, when it comes to Indigenous automobilities. Aboriginal people created tenacious and lively automobile cultures whenever and however they were able. While Aboriginal agency was far from erased, they were relegated to, and sometimes chose, historical silence. Automobility has been integral to imagining and materializing settler claims over the Australian continent, but also to evading, mitigating, contesting and re-visioning it.